Administrative Law - Peter Cane (2011)
This is the fourth edition of Peter Cane's Administrative Law, offering a straightforward but sophisticated account of an increasingly complex and important area of law, written in a lively and stimulating manner. The text, which has been extensively revised, takes full account of the many dramatic developments in English public law in recent years in areas such as devolution, human rights and freedom of information. The text has three mains aims: to provide a clear and concise account of the law concerning judicial control of public administrative power, to suggest political and theoretical perspectives that can help readers to understand the law better, and to explore the relationship between judicial and other forms of control such as ombudsmen and tribunals. An underlying theme of the analysis is to show that the role of courts in controlling public power is not that of neutral arbiter between 'citizen and state' but rather that of active participant in public decision-making processes.